2015
DOI: 10.1055/s-0035-1567805
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Rehabilitation Techniques in Children with Poor Prognosis Short Bowel Syndrome

Abstract: Intestinal failure (IF) requires a multidisciplinary management based on nutritional support, surgical and medical rehabilitation, and transplantation. The aim of this study is to review our experience with surgical rehabilitation techniques (SRTs: enteroplasty, Bianchi, Serial Transverse Enteroplasty Procedure [STEP]) in patients with short bowel syndrome (SBS) and poor prognosis due to complex abdominal pathology. We performed a single-center retrospective study of patients with IF evaluated for intestinal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…El tratamiento quirúrgico debe de ser resolutivo, pero a su vez conservador (24,25) . El cirujano pediátrico no debería precipitarse en tomar decisiones irreversibles; ante la duda sobre la viabilidad del intestino, es preferible realizar intervenciones de "second-look", o realizar un estoma temporal.…”
Section: Tratamiento Quirúrgicounclassified
“…El tratamiento quirúrgico debe de ser resolutivo, pero a su vez conservador (24,25) . El cirujano pediátrico no debería precipitarse en tomar decisiones irreversibles; ante la duda sobre la viabilidad del intestino, es preferible realizar intervenciones de "second-look", o realizar un estoma temporal.…”
Section: Tratamiento Quirúrgicounclassified
“…Surgical treatment should allow for resolution while being conservative (24,25) . Pediatric surgeons should not take irreversible decisions.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Dore et al showed that intestinal adaptation was achieved in 41% of children with SBS, but a trend towards a poorer outcome was observed in cases with USBS. 24 Lengthening procedures should therefore be reserved for specially selected cases of USBS. 7 …”
Section: Introductionmentioning
confidence: 99%